Hybrid Model of Teaching-Learning is Total Chaos : An Effect of Reverse Halo - Bakhare, Ruhi (Journal of Engineering Education Transformations, 2022)
Although the COVID-19 outbreak has had a disruptive impact on the education industry; the academicians have moulded themselves according to changing situations. They have evolved to an entirely different level during the last two years. This longitudinal study is conducted on faculty members from all over India and aimed to explore some individual and organizational factors affecting the â€œHybridâ€ model of the teaching-learning process, which is the future of the education and training industry [1] [2] creating a Reverse Halo Effect [3]. More than 1000 faculty members from all over India have contacted over WhatsApp and a self-report questionnaire in the form of Google Form measuring various student-related factors, institute-related issues, faculty-related issues, technology-related issues, perceived learning, and perceived employability was circulated. A path analysis showed that the student-related issues, faculty-related issues, institute-related issues, and technology-related issues affect perceived learning which will eventually affect the perceived employability of students. The findings of this study provide a theoretical contribution toward the effectiveness of the hybrid model in the teaching-learning process and its effect on the perceived learning and employability of students.